Análise da escrita manual de escolares do ensino fundamental: elaboração de um protocolo de avaliação educacional - Cardoso, Monique Herrera [UNESP] (2019)
This study aimed to establish a Handwriting Proficiency Test (TPEM) for primary school students, aged 9 to 14 years, which evaluates three areas: legibility and speed of handwriting, fine motor and visual-motor perceptual skills. Therefore, it presented in the form of two studies. Study 1 aimed to prepare the test. As a method was done to see how bibliographic are currently made the evaluation of handwriting, the visual-motor perceptual and fine motor skills. From then, it was elaborated the procedure and conducted the pilot study. As a result of the study 01 appeared 13 tasks divided into three battery, five tasks involving the assessment of legibility and speed of the handwriting to the evaluation of battery handwriting (BAT-EM), five tasks for the battery fine motor skill (BATFMF) and three tasks for visual-motor perceptual battery (BAT-PVM). The pilot study proved to be easy to apply and well understood by schoolchildren, generating small modifications to the final version. After completing the preparation of the test, study 02 was started, which aimed to characterize the profile and compare the performance of elementary school students I and II in the TPEM and also to verify if there is a relation between the three batteries of the TPEM. The study 02 included, 210 students enrolled in the 3rd to 9th grade of elementary school, aged between 09 years to 14 years and 11 months, of both genders, which were divided into 6 groups by age (38 children aged 9 years, 44 schoolchildren aged 10 years, 40 schoolchildren aged 11 years, 39 schoolchildren aged 12 years, 24 schoolchildren aged 13 years and 25 schoolchildren aged 14 years). TPEM was applied in a group for BAT-EM (except task 01, since it was collected individually) and for BAT-PVM, using 50 minutes for each of the batteries, since BAT-FMF was performed individually, not exceeding the total of 15 minutes, totaling 115 minutes for total application of the test. The written samples were analyzed for legibility and writing speed and the performance of BAT-PVM and BAT-FVM tasks were analyzed, for the most part, by likert scales. The results were statistically analyzed and showed a difference between 9 and 10 year old students when compared to the other groups, in almost all analyzes. It was also possible to find relationships between BAT-PVM and BAT-FMF and the writing tasks. The results show that the elaborated test can be effective to evaluate and characterize handwriting, visual-motor perceptual and fine motor skills of the students of this study, indicating that it can be an aid instrument for both teachers and for clinical professionals who work in the area of education.